1999
DOI: 10.1021/tx9802217
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Human Hepatic Cytochrome P450s 2C9 and 3A4 in the Metabolic Activation of Diclofenac

Abstract: Recently, it was shown that diclofenac was metabolized in rats to reactive benzoquinone imines via cytochrome P450-catalyzed oxidation. These metabolites also were detected in human hepatocyte cultures in the form of glutathione (GSH) adducts. This report describes the results of further studies aimed at characterizing the human hepatic P450-mediated bioactivation of diclofenac. The reactive metabolites formed in vitro were trapped by GSH and analyzed by LC/MS/MS. Thus, three GSH adducts, namely, 5-hydroxy-4-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(89 citation statements)
references
References 20 publications
7
82
0
Order By: Relevance
“…Because CYP3A4, a major component of diclofenac 5-hydroxylation (Shen et al, 1999;Tang et al, 1999b), was selectively inactivated, it is reasonable to postulate that the 5-hydroxylation pathway of diclofenac is responsible for the inactivation of CYP3A4. Because recent reports (Tang et al, 1999a;Ngui et al, 2000) showed that diclofenac 5-hydroxylation was stimulated by quinidine, the effect of the simulation on the inactivation of CYP3A4 was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because CYP3A4, a major component of diclofenac 5-hydroxylation (Shen et al, 1999;Tang et al, 1999b), was selectively inactivated, it is reasonable to postulate that the 5-hydroxylation pathway of diclofenac is responsible for the inactivation of CYP3A4. Because recent reports (Tang et al, 1999a;Ngui et al, 2000) showed that diclofenac 5-hydroxylation was stimulated by quinidine, the effect of the simulation on the inactivation of CYP3A4 was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…CYP2C11 was shown to be responsible for major diclofenac metabolisms, 4Ј-hydroxylation and 5-hydroxylation ( Fig. 1), in rat liver microsomes (Masubuchi et al, 2001), whereas distinct P450 isoforms, CYP2C9 and CYP3A4, were involved in these pathways, respectively, in human liver microsomes (Leemann et al, 1993;Shen et al, 1999;Tang et al, 1999b). Because CYP2C9 was not inactivated during diclofenac metabolism (Masubuchi et al, 2001), it was suggested that the inactivation of CYP2C11 was independent of 4Ј-hydroxylation pathway, supposing alternatively that 5-hydroxylation is involved in the inactivation of CYP2C11.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Tang et al (1999b) observed that the formation of diclofenac metabolites via CYP3A4 increased more than 4-fold in human liver microsomes in the presence of quinidine. Since similar results were seen in monkey liver microsomes, Tang and coworkers (1999a) followed this work with an in vivo study in monkeys and observed that in the presence of quinidine, diclofenac clearance was enhanced in three male rhesus monkeys by 57, 56, and 56%, respectively.…”
Section: In Vivo Considerationsmentioning
confidence: 94%
“…These drugs are metabolised by more than one CYP isoform: acetaminophen is metabolised by CYP isoforms 1A2, 2A6, 2D6, 2E1 and 3A4 (Patten et al, 1993); diclofenac by CYPs isoforms 2C9 and 3A4 (Tang et al, 1999) and chloroquine is metabolised by CYP2C8, 2D6 and 3A4/5 (Ducharme and Farinotti 1996; Kim et al, 2003). Drugs metabolised by more than one CYP isoforms or drugs that have other dominant metabolic pathways such as glucoronidation and sulphoxidation may not be significantly affected by inhibitors of only one of the CYP isoform since there is an alternate route of metabolism except if the inhibitor is able to inhibit all the metabolic pathways of the drug concerned.…”
Section: Discussionmentioning
confidence: 99%